To determine whether the system of equations is consistent and independent, consistent and dependent, or inconsistent, we need to first solve the system of equations to find the value of x and y that satisfy both equations.
To solve the system of equations, we can first solve the first equation for y:
y = −3x + 1
Next, we can substitute this expression for y into the second equation and solve for x:
2y = −6x + 2
2 * (−3x + 1) = −6x + 2
−6x + 2 = −6x + 2
0 = 0
Since the two equations are equivalent, the system of equations is consistent and dependent, meaning that there is only one possible solution (x = 0, y = 1) that satisfies both equations.